Electricity Energy Consumption Forecasting Using Different Deep Learning Models - Salih Rasul, Karwan; Abdulqadir Ali, Nzar (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
Accurate forecasting of electricity energy requirements has become critical for current energy systems, which are facing increasing challenges due to industrial development, population growth and the integration of green energy. The research evaluates the capacity of machine learning and deep learning algorithms to forecast demand of electricity energy consumption using dataset information from central electricity control office of Iraqi Kurdistan Region Government (KRG). Electricity energy consumption data analysis requires predictive models that are more sophisticated than traditional methods such as Autoregressive Integrated Moving Average (ARIMA) and exponential sequences, as these methods fail to deal with complex nonlinear patterns and high-frequency oscillations. Therefore, this study presents deep learning models using Long Short-Term Memory (LSTM) and Recurrent Neural Network (RNN), where the test results on the electricity energy data from KRG showed the superiority of the LSTM model in terms of accuracy and stability compared to RNN, the data was analyzed using multiple performance measures such as Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) to confirm the efficiency of the proposed model. The results show LSTM superior performance than the RNN model based on the metrics provided, as the RMSE (187.25) and MAE (139.78) values are lower compared to the RNN (RMSE = 230.34, MAE = 232.276), indicating that LSTM forecasts are more accurate with fewer errors. In addition, the coefficient of determination (R²) of the LSTM model (0.961) is higher than that of RNN (0.941) Finally, this model can be applied in intelligent energy systems to improve load management efficiency and reduce waste.